Continuous urinary incontinence secondary to bilateral intramural ureteral ectopia in a female Shiba inu canine - Case report (Research, Society and Development, 2020)
The purpose of this report is to describe the diagnosis and surgical treatment of bilateral ureteral ectopia, in a Shiba Inu dog, with resolution of the clinical sign of persistent urinary incontinence. Ureteral ectopia is a congenital anomaly, resulting from a failure in renal embryogenesis. Among the types of ectopic ureter, the intramural is classified in which the ureter is located on the dorsal or dorsolateral surface of the bladder, usually passing through the submucosa to open in the urethra or in the vagina and, the extramural, those that completely go beyond the bladder.  It was possible to verify the presence of ureteral alteration by means of tomographic examination, where the ectopic insertion of the ureters in the contrast was noted. Thus, with the confirmation of the diagnosis, the patient was referred to the surgical procedure performed with the aid of urethroscopy and the technique of laser ureteral ablation was performed. There was an improvement in the clinical complaint of incontinence after the procedure. Therefore, in the presence of persistent or intermittent urinary incontinence in young animals, congenital ureteral ectopia should be included in the differential diagnosis.